Terahertz cherenkov radiation excited by an electron beam in a cylindrical metallic rippled-wall waveguide - Asadiamiri, F.; Ali, J.; Bahadoran, M.; Chaudhary, K.; Yupapin, P. P.; Nejati, M.; Niknam, A. R. (My University, 2020)
The Cherenkov excitation of terahertz (THz) radiation by the interaction of an electron beam with the transverse magnetic modes of electromagnetic waves in a new configuration of cylindrical metallic rippled-wall waveguide (CMRWW) including an unmagnetized degenerate plasma layer and a dielectric rod is studied. In addition, the electric field profiles and the growth rates of these waves are investigated by deriving the wave equation and the dispersion relation for the proposed configuration. The effects of physical parameters such as dielectric and plasma radii, corrugation amplitude, and corrugation period on the dispersion relation, electric field profiles and growth rates of the terahertz radiation are discussed. It is shown that by choosing appropriate parameters of the electron beam and the waveguide, one can generate high power radiation in the terahertz range.
Keywords: Dispersion relation; Excitation; Growth rate; Rippled-wall waveguide; Unmagnetized degenerate plasma